2008
DOI: 10.1186/1471-2164-9-444
|View full text |Cite
|
Sign up to set email alerts
|

Using gene expression databases for classical trait QTL candidate gene discovery in the BXD recombinant inbred genetic reference population: Mouse forebrain weight

Abstract: Background: Successful strategies for QTL gene identification benefit from combined experimental and bioinformatic approaches. Unique design aspects of the BXD recombinant inbred line mapping panel allow use of archived gene microarray expression data to filter likely from unlikely candidates. This prompted us to propose a simple five-filter protocol for candidate nomination. To filter more likely from less likely candidates, we required candidate genes near to the QTL to have mRNA abundance that correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…VMB iron and VMB DA transporter (DAT) density were positively correlated, consistent with the previous report that iron deficiency reduces the protein density of DAT in the rat VMB [15]. VMB iron and several anxiety and depression-related phenotypes were also correlated [29], in line with observations of increased anxiety and depression-related behaviors in iron-deficient rodents and humans [1, 22]. …”
Section: Resultssupporting
confidence: 88%
“…VMB iron and VMB DA transporter (DAT) density were positively correlated, consistent with the previous report that iron deficiency reduces the protein density of DAT in the rat VMB [15]. VMB iron and several anxiety and depression-related phenotypes were also correlated [29], in line with observations of increased anxiety and depression-related behaviors in iron-deficient rodents and humans [1, 22]. …”
Section: Resultssupporting
confidence: 88%
“…Furthermore, it combines experimental data and bioinformatics approaches of different experiments to facilitate the identification of candidate genes [61]. Initially, we selected the genes, which are physically located in the target QTL interval with the highest test statistic.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the genetic and functional diversity of mouse strains can also be useful in identifying the molecular underpinnings of complex traits, as well as in defining a broader molecular and physiological impact of medications. Essential to this strategy is the presence of genetic or functional variation between strains that can be exploited to identify heritable influences (Holmes et al, 2002; Lu et al, 2008). We identified coding variation in SERT between C57BL/6J (Gly39 and Lys152=GK haplotype) and DBA/2J (Glu39 and Arg152=ER haplotype) and, using heterologous expression studies, demonstrated that this sequence variation imparted significant differences in 5-HT transport capacity (Carneiro et al, 2009) (Fig.…”
Section: Strain-based Genetic Variation In Mouse Sert and Its Use In mentioning
confidence: 99%
“…The dense genotyping of the BXD lines, along with the full sequencing of the parental genomes, provides the researcher with a powerful paradigm to map quantitative trait loci (QTLs) supporting functional variation (Lu et al, 2008; Gaglani et al, 2009). Additionally, correlations can also be identified between biochemical or functional traits due to their co-segregation across BXD lines, and then their common genetic underpinnings can be pursued (Koutnikova et al, 2009; Tapocik et al, 2009).…”
Section: Strain-based Genetic Variation In Mouse Sert and Its Use In mentioning
confidence: 99%